PELAKSANAAN UPACARA ADAT BESAMSAM MASYARAKAT DAYAK SALAKO DI DESA BUKIT SEGOLER KECAMATAN TEBAS KABUPATEN SAMBAS - NIM. A1011201262, ANISA OKTAVIA (Fakultas Hukum Universitas Tanjungpura, 2024)
ABSTRACT The Besamsam traditional ceremony is a traditional ceremony carried out by closing the village with the main aim of preventing reinforcements or anything that is considered evil from entering the village. The Besamsam traditional ceremony is a hereditary tradition passed down from generation to generation, carried out as a form of request to Jubata (God) and the spirits of the ancestors to protect their area. This research reveals a shift in the implementation of the Besamsam Traditional Ceremony in Bukit Segoler Village, Tebas District, Sambas Regency. This shift is influenced by changing factors over time. One of the shifts in the implementation of traditional besamsam ceremonies is that traditional besamsam ceremonies are no longer held once a year, and traditional sanctions equipment can be replaced with money. The formulation of the problem in this research is